Deusas que riem: performance-sagrada e ancestralidade feminina a partir do arquétipo das pombagiras - Miranda, Helder Carlos de (2022)
This work is aimed at developing, analyzing and ref lecting on a practical artistic proposal that that dialogues with aesthetic, philosophical and social knowledge belonging to Af ro-Brazilian religions. The study carried out permeates intersections between the theatrical comic (laughter in the theater) and the feminine deities of Candomblé and Umbanda, especially the Pombagira entity. It addresses a practical and theoretical investigation of aesthetic and poetic elements carried out by these deities. Currently, several artistic experiments have been promoted as a ref lection of the Af ro-Brazilian culture, both as a movement for the preservation of culture, as well as a process of cultural resistance in the f ight against racism. In line with these perspectives, it was developed through experience and participation with Companhia do Intéprete and in sacred rituals in Umbanda yards, as well as through interviews with the pai & mãe-de-santo f rom the Ilê Ase Igba Ty Oya Balé Umbanda yard. The results were analyzed through the creation, realization and analysis of the sacred performance “Laughter and Ancestry: The Feminine”. This sacred perf ormance was carried out based on f ield research, especially based on the archetype of the Pombagira entity in the dialogue with the experiences already def ined by the collective of artists of Companhia do Intérprete with laughter and theatrical comic. By living and experiencing attributes of black culture and religiosity, it is clear that, with them, it is possible to compensate for creative practices. These practices, in addition to contributing to the anti-racist struggle and Af ro-Brazilian resistance processes, can extrapolate hegemonic, white and European-centered references.